A intersemiose texto-história-cinema na minissérie ROMA da HBO - Prado, João Batista Toledo [UNESP] (My University, 2012)
From August 2005 to March 2007, the two seasons (with 12 and 10 episodes respectively) of the award winning miniseries HBO‟s ROME were aired by the Home Box Office (HBO) channel. With screenplay signed by various writers and directors, the TV series was a coproduction of HBO (USA) and BBC (UK) with support from RAI (Italy), and the show was filmed in multiple locations, but mainly in Cinecittà Film Studios in Rome, very famous for having been headquarters also for Federico Fellini‟s movies. In the first season, the miniseries depicts the conquest of Gaul, made by the military genius of Gaius Julius Caesar, and the political trajectory that made him accumulate power to such an extent that this divided Roman citizens into two factions, one supporting and the other opposing him, the latter focused mainly on the historic figure of General Gnaeus Pompey Magnus. The second season shows the period of civil war following the assassination of Caesar, and the future rise to power of his nephew, adopted son and sole heir, Gaius Octavian Augustus, who was destined to overcome his rivals as well as their allies in the triumvirate that had been formed to pursue and punish Caesar‟s assassins. These facts are well known and usually crowd the mind and imagination of every minimally educated person. The HBO series broke new ground not only for the talent of its writers, directors and actors, not only for its visual effects and locations nor for the vibrancy and grandeur of historical scenes – after all, “historical movies” in general do the same – but it has done so also by the (re)construction of historical events from the perspective of a pair of protagonists of whom too little is known: the centurions Titus Pullo and Lucius Vorenus, who are the only low-rank soldiers mentioned by Caesar in his book Commentaries on the Gallic War (Commentarii de Bello Gallico V.44). Thus, the fictionalization of events also took into account several Roman civilization data which were scattered through historical sources and also those that belong to the modern knowledge of material culture, resulting in a TV series whose filmic aesthetics has rare beauty and creativity. From the survey of textual, historical and cultural data put together in this film, as well as the distance featuring the creative space in the dimension of the gap between them, this paper aims to highlight two pivotal moments of visual and narrative strategies of the show: the opening credits footage and the final scenes of the first season of HBO's Rome.

Entre agosto de 2005 e março de 2007, foram exibidas as duas temporadas da premiadíssima minissérie ROMA, com 12 e 10 episódios respectivamente, no canal de TV por assinatura da Home Box Office (HBO). Com história assinada por vários roteiristas e diretores, coprodução da própria HBO (EUA) e BBC (Reino Unido), com apoio da RAI (Itália), e filmada em múltiplas locações, mas principalmente nos estúdios cinematográficos de Cinecittà, em Roma, célebres por terem sido sede também da obra de Federico Fellini, a minissérie retrata, na primeira temporada, a conquista das Gálias, empreendida pelo gênio militar de Caio Júlio César, e a trajetória política que o fez acumular poder de tal forma a dividir os cidadãos romanos em duas facções, uma que o apoiava, outra que o combatia, centrada sobretudo na figura do general Cneu Pompeu Magno; a segunda temporada mostra o período da guerra civil que sucedeu ao assassinato de César, com a ascensão ao poder de seu sobrinho, filho adotivo e único herdeiro, Caio Otávio Augusto, após ter sobrepujado seus rivais bem como seus aliados no triunvirato que se havia formado para perseguir e punir os assassinos de César. Tais fatos são sobejamente conhecidos e povoam a mente e a imaginação de todos os minimamente escolarizados. Assim mesmo, a série da HBO inovou não apenas pelo talento de roteiristas, diretores e atores, nem somente pelos efeitos visuais, locações, vivacidade e grandiosidade das cenas históricas – afinal, “filmes de época” em geral fazem o mesmo – mas também pela (re)construção de eventos históricos a partir da ótica de uma dupla de protagonistas dos quais pouco se conhece: os centuriões Tito Pullo (ou Pulão) e Lúcio Voreno, únicos soldados nomeados por César na obra Comentários sobre a Guerra das Gálias (Commentarii de Bello GallicoV.44). Por isso, a ficcionalização dos eventos levou em conta também diversos dados de civilização romana dispersos em obras historiográficas e que fazem parte do conhecimento moderno de cultura material, resultando num seriado de TV com estética fílmica de rara beleza e criatividade. A partir do levantamento de dados textuais, históricos e culturais reunidos na recriação fílmica do seriado, bem como da distância que caracteriza o espaço criativo na dimensão do intervalo entre eles, este trabalho objetiva salientar dois momentos privilegiados das estratégias visual e narrativa do seriado: a sequência dos créditos de abertura e as cenas finais da primeira temporada de Roma da HBO.
The text-history-cinema intersemiosis in hbo’s Rome
Keywords: Intersemiotic Relations; HBO‟s Rome TV series; De Bello Gallico; Material Culture; Opening and final footages; Relações Intersemióticas; Seriado Roma (HBO); De Bello Gallico; Cultura Material; Sequências de abertura e final